Pengaruh Pengalaman Pelanggan dan Inovasi Produk Terhadap Kepuasan Pelanggan - Bernard Vandra Saputra Pandie; Yusak Prakoso (Jurnal Minfo Polgan, 2026)
This study aims to analyze the influence of customer experience and product innovation on customer satisfaction at The Bridge Coffee and Eatery. The study uses a quantitative approach with data collection techniques through distributing questionnaires to 96 respondents using a random sampling method. Data were analyzed using SPSS 32 through validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination tests. The results show that customer experience has a positive and significant effect on customer satisfaction with a significance value of 0.036. Product innovation also has a positive and significant effect on customer satisfaction with a significance value of 0.001. Simultaneously, customer experience and product innovation have a significant effect on customer satisfaction with a calculated F value of 45.645 and a significance of 0.001. The R Square value of 0.495 indicates that both variables are able to explain customer satisfaction by 49.5%, while the rest is influenced by other variables outside the study.